PERAN PASAR LELANG DALAM PEMASARAN CABAI DI KELOMPOK TANI LAHAN PASIR PANTAI KULON PROGO, YOGYAKARTA - Eksa Rusdiyana (Caraka Tani: Journal of Sustainable Agriculture, 2017)
This study aims to analyze the role of auction market institutions in marketing the chili by sand land farmer community in Kulon Progo Regency, Yogyakarta. This study was a quantitative study using questioner, interviews, and observations to collect the data. The results showed that the auction market institutions formed sand land farmer community had the effective roles in the marketing of chili including the exchange function, physical function, and the provision of infrastructure function. The existence of the auction market was able to increase the bargaining position of farmers to middlemen traders through the sale of the auction system. The concept of exchange theory in the marketing system of chili gave rewards toward the increasing of chili selling price and provided service marketing which made the work of farmers more effective. In addition, the auction market system gave sacrifices to farmers in the form of non-cash payments, but the auction market managers provided certainty of payment. The comparison between rewarded with the sacrifice still gave more value to the farmer's profit, it made the farmers repeating the marketing of chili through auction markets.